P. 1
Mathematics of the Discrete Fourier Transform

# Mathematics of the Discrete Fourier Transform

4.88

|Views: 1,529|Likes:

### Availability:

See more
See less

02/22/2013

pdf

text

original

We’ve now deﬁned az

for any positive real number a and any complex
number z. Setting a = e and z = jθ gives us the special case we need for

DRAFT of “Mathematics of the Discrete Fourier Transform (DFT),” by J.O.
Smith, CCRMA, Stanford, Winter 2002. The latest draft and linked HTML
version are available on-line at http://www-ccrma.stanford.edu/~jos/mdft/.

CHAPTER 3. PROOF OF EULER’S IDENTITY

Page 35

Euler’s identity. Since ez

is its own derivative, the Taylor series expansion

for for f(x) = ex

is one of the simplest imaginable inﬁnite series:

ex

=

∞ n=0

xn

n! = 1 +x+ x2

2 + x3

3! +···

The simplicity comes about because f(n)

(0) = 1 for all n and because we

chose to expand about the point x = 0. We of course deﬁne

ejθ ∆

=

∞ n=0

(jθ)n

n! = 1 +jθ−θ2

/2−jθ3

/3! +···

Note that all even order terms are real while all odd order terms are
imaginary. Separating out the real and imaginary parts gives

re

ejθ

= 1−θ2

/2 +θ4

/4!−···

im

ejθ

= θ−θ3

/3! +θ5

/5!−···

Comparing the Maclaurin expansion for ejθ

with that of cos(θ) and

sin(θ) proves Euler’s identity. Recall that

d

dθ cos(θ) = −sin(θ)
d

dθ sin(θ) = cos(θ)

so that

dn

dθn cos(θ)

θ=0

=

(−1)n/2

, n even

0,

n odd

dn

dθn sin(θ)

θ=0

=

(−1)(n−1)/2

, n odd

0,

n even

Plugging into the general Maclaurin series gives

cos(θ) =

∞ n=0

f(n)

(0)

n! θn

=

∞ n≥0

neven

(−1)n/2

n! θn

sin(θ) =

∞ n≥0

nodd

(−1)(n−1)/2

n! θn

DRAFT of “Mathematics of the Discrete Fourier Transform (DFT),” by J.O.
Smith, CCRMA, Stanford, Winter 2002. The latest draft and linked HTML
version are available on-line at http://www-ccrma.stanford.edu/~jos/mdft/.

Page 36

3.2. INFORMAL DERIVATION OF TAYLOR SERIES

Separating the Maclaurin expansion for ejθ

into its even and odd terms

(real and imaginary parts) gives

ejθ ∆

=

∞ n=0

(jθ)n

n! =

∞ n≥0

neven

(−1)n/2

n! θn

+j

∞ n≥0

nodd

(−1)(n−1)/2

n! θn

= cos(θ) +j sin(θ)

thus proving Euler’s identity.

scribd
/*********** DO NOT ALTER ANYTHING BELOW THIS LINE ! ************/ var s_code=s.t();if(s_code)document.write(s_code)//-->